Persistence of immune response to an adjuvanted varicella-zoster virus subunit vaccine for up to year nine in older adults - Schwarz, Tino F; Volpe, Stephanie; Catteau, Gregory; Chlibek, Roman; David, Marie Pierre; Richardus, Jan Hendrik; Lal, Himal; Oostvogels, Lidia; Pauksens, Karlis; Ravault, Stephanie; Rombo, Lars; Sonder, Gerard; et al. (Human vaccines & immunotherapeutics, 2018)
BACKGROUND: In adults aged ≥60 years, two doses of the herpes zoster subunit vaccine (HZ/su; 50 µg varicella-zoster virus glycoprotein E [gE] and AS01B Adjuvant System) elicited humoral and cell-mediated immune responses persisting for at least six years. We assessed immunogenicity nine years post-initial vaccination. METHODS: This open extension study (NCT02735915) followed 70 participants who received two HZ/su doses in the initial trial (NCT00434577). Blood samples to assess the cellular (intracellular cytokine staining) and humoral (ELISA) immunity were taken at year nine post-initial vaccination. RESULTS: Participants' mean age at dose 1 was 72.3 years. The fold increases over pre-vaccination in the mean frequency of gE-specific CD4+ T-cells expressing ≥2 activation markers plateaued from year four post-dose 1 until year nine. Anti-gE antibody geometric mean concentrations plateaued and remained above pre-vaccination levels from year four onwards. Immunogenicity at year nine was similar across age strata (60-69, ≥70 years) and confirmed statistical prediction model results using data for up to year six. Further modeling using all data up to year nine predicted immune responses would remain above the pre-vaccination level up to year 15. CONCLUSION: In adults aged ≥60 years, HZ/su-induced immunogenicity remained above pre-vaccination levels for at least nine years post-initial vaccination. SUMMARY: After vaccination with HZ/su, both cell mediated and humoral immunity remained above pre-vaccination levels up to year 9 regardless of age group. Immune responses are predicted to remain above baseline up to 15 years post initial vaccination.
Keywords: prediction modeling; dospělí; immunity; Cytokines; herpes zoster; Adult; Lipid A; Herpes Zoster Vaccine; cytokiny; časové faktory; Time Factors; lidé; virus varicella zoster; Aged, 80 and over; následné studie; Herpesvirus 3, Human; herpes zoster (shingles) vaccine; vakcína proti pásovému oparu; T-lymfocyty; persistence; protilátky virové; kohortové studie; Cohort Studies; varicella-zoster virus; subunit gE vaccine; Follow-Up Studies; Aged; Vaccines, Subunit; lipid A; subjednotkové vakcíny; lidé středního věku; senioři nad 80 let; senioři; T-Lymphocytes; Antibodies, Viral; Saponins; Middle Aged; prevention; saponiny; Humans